Evaluation of confirmatory data following the Article 12 MRL review and modification of the existing maximum residue levels for prothioconazole in celeriacs and rapeseeds. (21st February 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicants Bayer SAS Crop Science and the Agriculture and Horticulture Development Board submitted two requests to the competent national authority in the United Kingdom to modify the existing maximum residue levels (MRLs) for prothioconazole in rapeseeds and celeriacs, respectively. The data submitted in support of the requests were found to be sufficient to derive MRL proposals for these crops. The applicant Bayer SAS Crop Science additionally submitted a request to the competent national authority in the United Kingdom to evaluate the confirmatory data identified in the framework of the MRL review under Article 12 of Regulation (EC) No 396/2005 as not available. To address the data gaps, residue trials on carrots, onions, rapeseeds and wheat, and storage stability studies were submitted. The data gaps are considered fully addressed for the root and tuber vegetables, the oilseeds concerned and wheat. The data gaps have been partially addressed for onions, shallots, flowering brassica, Brussels sprouts, head cabbages, leeks, rye, barely and oat. The data gaps were not addressed for pulses and grass. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the existing and intended uses of prothioconazole according to the reported agricultural practices is unlikely to present a risk to consumer health. For the triazole derivative metabolites (TDMs), only an indicative exposure assessment was performed considering celeriacs and rapeseeds; the results showed that the expected exposure to TDMs in these commodities is well below the toxicological reference values derived for the TDMs.